Impact of Preexisting Cognitive Impairment and Race/Ethnicity on Functional Outcomes Following Intracerebral Hemorrhage. Issue 2 (February 2021) - Sawyer, Russell P.; Yim, Eunji; Coleman, Elisheva; Demel, Stacie L.; Sekar, Padmini; Woo, Daniel
Abstract : Background and Purpose: In intracerebral hemorrhage (ICH), preexisting cognitive impairment has been identified as a risk factor for increased mortality and morbidity. However, previous studies examined predominantly White populations; therefore, the prevalence and effect of preICH cognitive impairment has not been studied in a multiethnic cohort. This limits the generalizability of previous findings. We sought to investigate the role of preexisting cognitive impairment in a multiethnic population on short-term mortality and functional outcomes after ICH. Methods: Patients with ICH were prospectively enrolled as cases for the GERFHS III (Genetic and Environmental Risk Factors for Hemorrhagic Stroke) Study and the Ethnic/Racial Variations of ICH (ERICH) Study. Cognitive impairment before ICH was defined as positive history of dementia or treatment with donepezil, galantamine, memantine, or rivastigmine on chart abstraction or baseline interview. Specific outcomes—modified Rankin Scale score at 3 months (0–2 versus ≥3), Barthel Index score (<100 versus 100) at 3 months, and withdrawal of care—were analyzed using multivariable logistic regression. Propensity score matching and analysis was done because of imbalances between cognitively impaired and cognitively intact groups. Results: Of the 3537 cases of ICH, 304 patients had cognitive impairment predating ICH. Cognitively impaired subjects were more likely to experience withdrawal of care during hospitalization, and for survivors, greater disability (modified Rankin Scale score of ≥3) and lower Barthel scores after ICH. After propensity score matching, preexisting cognitive impairment was associated with a lower modified Rankin Scale at 3 months in the White, Black, and Hispanic subgroups. Conclusions: Preexisting cognitive impairment was associated with loss of independence 3-month post-ICH, when matching for risk factors of cognitive impairment, in the White, Black, and Hispanic subgroups. This suggests that preexisting cognitive impairment has a negative effect in obtaining functional independence following ICH, irrespective of race/ethnicity.